Penerapan Akuntansi Manajemen Sebagai Mediator Pengaruh Sikap Keuangan dan Pengetahuan Keuangan Terhadap Kinerja Keuangan Usaha Kecil Menengah (UKM) (Studi Kasus Pada UKM yang Terdaftar di Dinas Koperasi, Usaha Kecil Menengah, Perindustrian, dan Perdagangan Kabupaten Lumajang) - Rohmah, Wahyu Azizatur; Maslichah, Maslichah; Hidayati, Irma (Universitas Islam Malang, 2024)
This research aims to analyze the application of accounting as a mediator of the influence of financial attitudes and financial knowledge on the financial performance of SMEs. This study is an explanatory research with a quantitative approach, using primary data obtained from questionnaires and measured using the Likert Scale. The data analysis method used is Partial Least Squares, processed using SmartPLS 24 software. The population in this study consists of Small and Medium Enterprises registered with the Department of Cooperatives, Small and Medium Enterprises, Industry, and Trade of Lumajang Regency. Data were collected from 91 respondents through questionnaires given to SME owners, using purposive sampling techniques. The results of the analysis indicate that financial attitudes and financial knowledge have a significant influence on the financial performance of SMEs, financial attitudes and financial knowledge have a significant influence on the application of management accounting in SMEs, the application of management accounting does not have a significant influence on the financial performance of SMEs, and the application of management accounting does not mediate financial attitudes towards the financial performance of SMEs.Keywords: Financial performance, financial attitudes, financial knowledge, application of management accounting